Provisions of Legal Protection for Terrorism Victim in Order to Realize Constitution Order - Ismail Koto; Taufik Hidayat Lubis; Soraya Sakinah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
The purpose of this study is to find out how to provide legal protection for victims of terrorism crimes in order to realize constitutional orders. The type of this research is descriptive analytical. This research is carried out by examining theories, concepts, legal principles, the systematics of laws, legal comparisons and legal history, and synchronization of laws and regulations. Terrorism can happen anytime, anywhere, and happen to anyone indiscriminately. The damage caused by acts of terrorism is enormous. The rise of terror that occurred with many victims has proven that terrorism is a crime against human values. Terror has proven as a matter of fact as a tragedy over human rights. The physical impact caused by terrorism is not only on those who are targeted but also on victims who do not know and are not related to the target of the terrorist. Article 35A, paragraph 1 under Act No. 5 of 2018 stated that â€œVictims are state responsibilityâ€. By the presence of state to handle terrorismâ€™s victim, it is hoped that more targeted and equitable rights of all victims affected by an act of terrorism.